Some Notes on City Income Levels - Mansfield, Edwin (The Review of Economics and Statistics, 1956)
rfHERE has been considerable interest in 1the spatial aspects of the income distribution. Many studies have attempted to measure inter-area differences in income level and to investigate the factors which could be responsible for them.' Most of these studies have dealt with income differences among regions or states, but in recent years increasing attention has been devoted to the city as another unit of study. In most cases, this attention has been confined to the city-size variable, its position vis-a-vis regional income differentials, and the factors responsible for its relation to the income level.2 In the I950 Census of Population, income data were collected for individual cities, and it became possible to measure intercity income differences and to test some hypotheses concerning them. Much of the variation in city income levels was found to be associated with the two variables that had often been singled out for attention: region and city-size. But a considerable amount of variation remained. Indeed, the variation in income level among cities of comparable size in the same region was often as great as the variation among the 48 states.3 Our interest here centers about this variation in income level among cities of comparable size in the same region. In formulating any complete model intended to explain the spatial distribution of income, this variation should be taken into account. To be complete, the model should explain this variation as well as the differences in income among regions and community-size categories. Information concerning differences among these cities should be useful in setting the stage for the construction of such a model.4 With regard to the differences in income among regions and community-size categories, considerable auxiliary information is available to guide the model-builder in his selection of variables. But this is not the case with respect to cities of comparable size in the same region. Attention here is focused on the intercity differences in the characteristics of the population. The particular population characteristics were chosen with the understanding that they are sometimes only indirectly connected with the factor markets and that an observed relationship between these characteristics and income does not necessarily establish a line of causation. Though the results can be little more than suggestive, they should provide some of the information that is needed.